Sports-related injuries sustained by disabled athletes in winter Paralympic games: A systematic review - Song, Y.; Zhang, W.; Zhao, L.; Sun, D.; Huang, Y.; Gu, Y. (Journal of Imaging and Health Informatics, 2020)
Purpose: This review aimed to analyze and summarize current literature related to the characteristics, incidence of injuries of different winter Paralympic sports events and to discuss the key aspects that can be used to develop possible prevention strategies for future Winter Paralympic Games. Methods: An electronic search was performed in Google Scholar, PubMed, and Web of Science databases using the following key words: "Paralympic" AND "winter sports" AND "injury" OR "prevention strategy." Inclusion and exclusion criteria were used to screening all the identified studies. Of 446 identified studies, 11 studies were included. Results: Most studies reported the injuries of disabled athletes in alpine skiing/snowboarding and ice sledge hockey, few studies reported injuries in cross-country skiing/biathlon and wheelchair curling. For these Winter Paralympic athletes, acute, traumatic injuries seem to be more common than overuse or chronic injuries, and alpine skiing and ice sledge hockey have always been the most dangerous winter sports events. However, the rates and injury locations appear to be disability and sport dependent. Results of this review demonstrated that there are 2 key areas in which specific prevention strategies would influence sports injuries and performance in Paralympic winter sports, namely, equipment in winter sports and physical condition of disabled athletes. Conclusion: According to the results, it is apparent that the overall injury rates sustained by disabled athletes are high and can be comparable with injury rates in able-bodied counterparts. While with few studies reported the pattern of injuries and possible prevention strategies, it is difficult to further understand the injury mechanisms and determine effective prevention strategies. Further longitudinal and disability specific studies are much needed.